A saliva α-glucosidase MpAgC2-2 enhance the feeding of green peach aphid Myzus persicae via extra-intestinal digestion. (November 2022) - Yang, Li; Tian, Yuan; Fang, Ying; Chen, Meng-Ling; Smagghe, Guy; Niu, Jinzhi; Wang, Jin-Jun
Abstract: Aphids feed on plant phloem sap that contains massive amounts of sucrose; this not only provides vital nutrition for the aphids but also produces high osmotic pressure. To utilize this carbon source and overcome the osmotic pressure, sucrose is hydrolyzed into the monosaccharides, glucose and fructose. In the green peach aphid ( Myzus persicae ), we show that this process is facilitated by a key α-glucosidase (MpAgC2-2), which is abundant in the aphid salivary gland and is secreted into leaves during feeding. MpAgC2-2 has a pH optimum of 8.0 in vitro, suggesting it has adapted to the environment of plant cells. Silencing MpAgC2-2 (but not the gut-specific MpAgC3-4 ) significantly increased the amount of sucrose ingested and hindered aphid feeding on the phloem of tobacco seedlings, resulting in a smaller body size, as well as lower α-glucosidase activity and glucose levels. These effects could be rescued by feeding aphids on tobacco plants transiently expressing MpAgC2-2 . The transient expression of MpAgC2-2 also led to the hydrolysis of sucrose in tobacco leaves. Taken together, these results demonstrate that MpAgC2-2 is a salivary protein that facilitates extra-intestinal feeding via sucrose hydrolysis. Our findings provide insight into the ability of aphids to digest the high concentration of sucrose in phloem, and the underlying mechanism of extra-intestinal digestion. Graphical abstract: Image 1 Highlights: MpAgC2-2 is a key α-glucosidase secreted into leaves by the green peach aphid. MpAgC2-2 and MpAgC3-4 work optimally in alkaline and acidic conditions, respectively. MpAgC2-2 silencing by RNAi inhibits the feeding performance of aphids. The MpAgC2-2 silencing effect is rescued by MpAgC2-2 expression in tobacco. MpAgC2-2 evolved as a key salivary protein to enhance extra-oral digestion.